An Enhanced Stability Nanoparticle Preparation by Corn Protein Hydrolysate‐Carboxymethyl Chitosan Maillard Conjugates Loaded with Rutin. Issue 7 (4th June 2019) - Han, Yue; Wang, Lixin; Jiang, Wenping; Du, Qijing; Yu, Chundi; Sun, Qingjie; Zhang, Shuangling
Abstract: Rutin‐loaded corn protein hydrolysate–carboxymethyl chitosan (CPH‐NOCC) Maillard conjugate nanoparticles (NPs) with superior stability under different NaCl concentrations (0–0.25 mol/L) and pH levels (7.0 to 3.0) were investigated. Results showed that the degree of glycosylation of 53.3%, browning index of 0.6, and SDS‐PAGE lane of CPH‐NOCC conjugates were obtained after dry heating for 48 hr (60 °C, 79% RH). The high encapsulation efficiency (EE, 97.8%–98.8%) and CPH‐NOCC‐rutin (98.8%) was significantly higher than CPH‐rutin (97.8%) and CPH/NOCC‐rutin (98.4%) NPs illustrated that hydrolysis was positive for zein encapsulation, and conjugation of NOCC to CPH increased the EE. Hairy carbohydrate protrusions on the surface of CPH‐NOCC‐rutin NPs produced a stronger steric effect and hampered the formation of salt bridges and the particle aggregation under CPH isoelectric point at pH 4.0. Therefore, the CPH‐NOCC conjugate NPs may be suitable carrier for hydrophobic bioactive substances in a board range of business foodstuffs.